Probing the physical conditions surrounding young star clusters. Issue Volume 14:Issue S345(2019) (August 2018) - Gregorio-Hetem, Jane; Fernandes, Beatriz; Navarete, Felipe
Abstract: The scenario of star cluster formation can be better understood based on the detailed study of the dynamical conditions of the associated gas, clustering properties and effects of ionizing sources, among others. Some of these characteristics are explored in our ongoing work based on observations with the SOAR and T80-S telescopes. With these data we have obtained a complete multi-band photometric catalogue of selected clusters that we characterize using color-color diagrams and flux ratios. In particular, this work is focused on SOAR/Spartan (near-infrared) observations of the Canis Major star-forming region.